(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: This study aims to assess the knowledge, attitudes, and practices (KAP) regarding reproductive health among students at Dong An High-Tech College in 2024 and explore associated factors. Methods: A cross-sectional study was conducted at Dong An High-Tech College from September to December 2024. The study included 430 full-time students from the 2021 cohort of the bridging program, selected using a convenience sampling method. Data were collected through a structured questionnaire comprising four sections: demographic information, knowledge, attitudes, and practices regarding reproductive health. The measurement scales were adapted from previous studies and adjusted for the study context. Results: Among the 430 surveyed students, 42.09% correctly understood the concept of reproductive health, while 29.07% had a comprehensive grasp of key aspects of reproductive health care. Additionally, 53.02% demonstrated accurate knowledge of contraceptive methods, whereas only 17.44% had a clear understanding of sexually transmitted infections (STIs). Attitudes toward reproductive health were generally positive, with 66.51% of students considering reproductive health highly important. However, varying opinions were observed regarding premarital sex and abortion. Pearson correlation analysis revealed a moderate positive relationship between knowledge and attitudes (r = 0.416, p < 0.001), whereas the correlation between attitudes and practices was weaker (r = 0.118, p = 0.014). These findings highlight the need for enhanced reproductive health education programs to improve students’ awareness and adoption of appropriate health practices. Conclusion: While students recognize the importance of reproductive health, their actual knowledge remains limited, particularly regarding contraceptive methods and STIs. A clear association was found between knowledge and attitudes, but attitudes had a limited impact on behavior. Therefore, reproductive health education should be strengthened to enhance students’ understanding and encourage appropriate health behaviors.